Social Identity and Economic Values: A Study of the Baiq and Lalu Clans in Increasing Sasak Traditional Wedding Dowry - Baiq Fera Susmita Putri; Lalu Sopan Tirta Kusuma; Azwar Subandi; Nur Hidayat Sardini (JURNAL ILMIAH DETUBUYA, 2025)
This study aims to develop a comprehensive synthesis of the dynamics of social identity and economic values ​​in Sasak traditional wedding dowry practices, with a focus on the role of the Baiq and Lalu clans in shaping social expectations and increasing dowry values. Using the Systematic Literature Review (SLR) method, this study examines literature indexed in Scopus, Google Scholar, and DOAJ for the period 2018–2025. The results indicate that dowry is a multidimensional construct that reflects complex interactions between cultural, social, and economic aspects, and plays a significant role in reinforcing social hierarchy through status symbols and cultural identity. The findings also indicate that most research is descriptive and has not systematically integrated cross-disciplinary approaches, leaving a gap in understanding the transformation of dowry values ​​amidst the currents of modernization. This study recommends three directions for further research: reinterpreting dowry values ​​by the younger generation, developing a dowry model based on social and economic justice, and examining the impact of cultural commercialization on the sanctity of customary practices. The theoretical and practical implications of this study are expected to enhance the understanding of local culture and support adaptive social policy reform grounded in traditional values.